Digital Tranformation and Impact on Organizational Change and Performance - Titis Sri Wulan; Putri Ayu Permata Devi; Deti Kurniati; Reni (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Digital transformation has become a key element in improving organisational performance and competitiveness. This research evaluates the impact of digital transformation on changes in organisational structure, culture, and performance through literature review and case study analysis. The results show that digital transformation drives significant changes in organisational structure, making it more flexible and collaborative. In addition, a culture that supports innovation and experimentation is shown to improve technological adaptation. Case studies from General Electric and Starbucks show that the implementation of digital technology can improve operational efficiency, productivity, and customer satisfaction. However, challenges such as resistance to change and lack of digital skills must be overcome. Solutions offered include intensive training, a phased approach to technology implementation, and investment in adequate infrastructure. As such, this research provides practical guidance for organisations that want to succeed in digital transformation and optimise their performance.